(untitled) (JURNAL PROTEKSI KESEHATAN, 2020)
Abstract Cervical Cancer or Uterine Carcinoma Cervicis, is the most malignant tumor and is most often found in women. Acetic Acid Visual Inspection Examination (IVA) is an examination for cervical cancer examination. Indragiri Hulu Regency is the highest positive IVA district, at 17.85%, from the number of women aged 30-50 years who are positive suffering from cervical cancer. The purpose of this study was to study the description of the knowledge of women of fertile age (WUS) about the inspection of visual acetate acid inspection (IVA) in Sungai Air Putih Village, Indragiri Hulu Regency. The research design used descriptive design. The sampling technique used was purposive sampling and random sampling with a total of 94 respondents. Data collection techniques by submitting questionnaires to married women of childbearing age (WUS) in Sungai Air Putih Village Sungai LalaPuskesmas Work Area in Indragiri Hulu Regency starting from 2-7 August 2018. Requesting research: finding inspection) less 63 WUS (67 %), enough 28 WUS (30%), and good 3 WUS (3%).